A comparison of maximal isometric force in the first pull, transition and second pull of the clean and their contribution to predict performance in national and international level weightlifters - Joffe, S. A.; Chavda, S.; Gilham, J.; Sandercock, G. R. H.; Tallent, J. (Sports Biomechanics, 2025)
This study aimed to examine differences in isometric peak force (PF) at the start of the first pull, transition, and second pull phases of the clean, and determine their contribution in explaining the variance in snatch and clean & jerk (C&J) performance. Thirty-one national and international level male and female weightlifters participated. Isometric start position pull (ISPP), isometric transition position pull (ITPP), and isometric mid-thigh pull (IMTP) PF, along with competition performance, were analysed both in absolute and allometrically scaled terms. Partial Least Squares Regression identified a single latent variable explaining 81.4% of the variance in Snatch and 79.6% in C&J. ISPP PF alone significantly contributed to explaining the variance the snatch and C&J. For allometrically scaled values, a single latent variable accounted for and 62.8% variance in Snatch and 60.7% of the variance in C&J, with ISPP PF significantly contributing to the Snatch and approached significance for C&J (p = 0.056). These results underscore the importance of evaluating maximal force in the initial lift phase and suggest that training to enhance strength in this phase may be crucial for improving weightlifting performance.